ChemInform Abstract: Catalytic Systems for Glycerol Oxidation: Alternatives for Waste Valorization. Issue 38 (30th August 2013) - Beltran‐Prieto, Juan Carlos; Kolomaznik, Karel; Pecha, Jiri
Abstract Review: 167 refs.